PEMBERIAN UANG PESANGON TERHADAP PEKERJA KONTRAK WAKTU TERTENTU YANG DIBERHENTIKAN PADA DINAS PERKEBUNAN PROVINSI BALI - Yudhi Pramadita, I Kadek; Markeling, I Ketut; Dedy Priyanto, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 03, Juni 2014, 2014)
The employment agreement is an agreement whereby the unity ( labor ) , bind themselves to work for a wage of both parties that the employer , and the employer binds itself to employ workers by paying wages . The employment agreement applies to contract workers , contract workers not only work on the company but also in government agencies , therefore the author will explain how the legal protection for a certain period of contract workers who were laid off and the provision of severance pay to a certain time contract workers who were laid off at the Department of plantation Bali Province . Study is a juridical empirical legal research . Legal protection for a certain period of contract workers who were laid off at the Plantation Office of Bali Province is not fully implemented and the granting of severance pay to contract workers who were laid off at a certain time Plantation Office of Bali Province is not implemented.
Keywords: Bargaining Agreement , Labor Contracts , Severance pay